In vitro anti-HIV-1 activity of the enzymatic extract enriched with laccase produced by the fungi ganoderma sp. and lentinus sp (2016)
ABSTRACT: Background: Natural compounds are a good source for the development of antiretroviral drugs with low cytotoxicity. The laccase enzyme, produced by fungi of the genera Ganoderma sp. and Lentinus sp., inhibits the reverse transcriptase (RT) of the human immunodeficiency virus 1 (HIV-1), in cell-free models in vitro. Objetives: In this study we evaluated the anti-HIV-1 activity of the enzymatic extracts (EE) enriched with laccase, produced by two native species of fungi of the same genera in an in vitro cell culture model. Methods: The inhibition of viral replication was performed using the U373-MAGI cell line infected with recombinant viruses in the presence/absence of the EE and 48 hpi, the percentage of infected cells was evaluated by flow cytometry for green fluorescent protein –GFP– and ELISA for p24. The inhibition of the RT was determined by quantification of early and late products of reverse transcription using quantitative PCR. Results: The EEs from Ganoderma sp. and Lentinus sp. inhibited the replication of HIV-1 between 80 and 90% and decreased the production of early and late transcripts between 55,5%-91,3% and 82,1%-93,6% respectively. The EE from Lentinus sp. had the best selectivity index (SI: 8.3). Conclusions: These results suggest the potential anti-HIV-1 activity of the EE for the exploration of an alternative therapy against HIV-1 infection.